Three approaches to community in restorative justice, explored through a young person's experiences of a youth offender team in England. Issue 2 (3rd May 2016) - Willis, Roxana
ABSTRACT: Restorative justice involves three categories of stakeholder: victims, offenders and community. Despite the apparent importance of community, what is meant by 'community' has received limited attention in restorative justice to date. This article contributes to efforts to bridge this gap by critically examining approaches to community in the restorative justice literature, in the context of wider theoretical community debates. Three approaches to community are identified: the community-of-care approach, which emphasises relational ties; the community-of-place approach, which emphasises geographical locality; and the danger of community, which highlights a dark side to community. The practical application of this theoretical framework is then demonstrated through an exploratory case study of a young person's experiences with a Youth Offender Team in England. By sharing an individual case study of multiple forms of restorative justice, and the effects of different approaches to community engagement, it is hoped this research will appeal to practitioners and academics alike.